ANALYSIS OF PROMOTIONAL EFFECTIVENESS USING SOCIAL MEDIA IN AGRO NADIIN TOURISM PARK IN SUNGAI PINANG, KAMPAR DISTRICT - Rakhmat Haryono; Librina Tria Putri; Winda Intan Sari (Jurnal Riset Manajemen Indonesia, 2023)
This study aims to determine whether or not the promotional activities carried out by the Agro Nadiin Sungai Pinang Tourism Park in Kampar Regency through social media using the EPIC Model analysis (emphaty, persuation, impact, communication) are analyzed separately using the average score method. to know the effectiveness of each dimension of social media. Promotion carried out by the Agro Nadiin Sungai Pinang Tourism Park, Kampar Regency, namely through social media Facebook, Instagram and YouTube. The population and samples were taken from 300 visitors to the Taman Wisata Agro Nadiin Sungai Pinang, Kampar Regency, using census techniques. Based on the research results, it can be concluded that the promotion carried out by the Taman Wisata Agro Nadiin Sungai Pinang, Kampar Regency has been effective.